The development of youth entrepreneurship in Krasnodar region - O. A. Martirosyan (Путеводитель предпринимателя, 2020)
Currently, there is an increased interest of youth to entrepreneurship, as a strategy of self-development, along with the growing desire ofyoung people in the constituent entities of the Russian Federation to participate in programs and projects that provide the opportunity to enhance entrepreneurial skills and start their own business. Krasnodar Krai plays the role of the leader in the number of subjects of small and average business, however, there are a number of problems in the development of youth entrepreneurship in the region